Studi dukungan sosial keluarga dengan perkembangan kemandirian emosional remaja usia sekolah menengah pertama full day school - Itsna Abidah Mardiyah; Tantut Susanto; Latifa Aini Susumaningrum (Journal of Community Empowerment for Health, 2019)
Early adolescents in high school with full-day school may not yet mature in emotional autonomy development. The purpose of this study is to analyze the correlation between family social support and emotional autonomy in adolescents aged junior high school full-day school in Districts of Jember. The design of this study is cross-sectional which is conducted among 154 adolescents aged 13-15 years with stratified random sampling. The questionnaire are self-administered questionnaires, participant characteristics, family social support (PSS-FA), and emotional autonomy (EAS) questionnaire. A Chi-square test was used to analyze to answer the research. Result shows that among adolescent have good family social support (70.8%) and high emotional autonomy (54.5%). There is a correlation between family social support and emotional autonomy of the adolescent with full-day school (X2=5.27; p-value=0.02). Adolescent with moderate family social support can prevent emotional autonomy immaturity (OR=0.427; 95% CI=0.205-0.891). Family social support is needed to develop maturity emotional autonomy among adolescents. Therefore, the parents need to give social support for adolescents during their change of development.